2013
DOI: 10.2174/13816128113199990333
|View full text |Cite
|
Sign up to set email alerts
|

The Control of Male Sexual Responses

Abstract: Male sexual responses are reflexes mediated by the spinal cord and modulated by neural circuitries involving both the peripheral and central nervous system. While the brain interact with the reflexes to allow perception of sexual sensations and to exert excitatory or inhibitory influences, penile reflexes can occur despite complete transections of the spinal cord, as demonstrated by the reviewed animal studies on spinalization and human studies on spinal cord injury. Neurophysiological and neuropharmacological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 0 publications
1
27
0
1
Order By: Relevance
“…NO, the primary neurotransmitter responsible for penile erection and clitoral engorgement, is released at nerve endings during sexual arousal and sexual stimulation (neuronal NO or nNO) and is also made in the endothelium itself (endothelial NO or eNO). 3 With the release of nNO at the nerve endings of the genital nerve fibers during sexual arousal, smooth muscle relaxation is initiated. The health of the endothelium will determine the contribution of eNO to the erectile process.…”
Section: Genital Arousalmentioning
confidence: 99%
See 1 more Smart Citation
“…NO, the primary neurotransmitter responsible for penile erection and clitoral engorgement, is released at nerve endings during sexual arousal and sexual stimulation (neuronal NO or nNO) and is also made in the endothelium itself (endothelial NO or eNO). 3 With the release of nNO at the nerve endings of the genital nerve fibers during sexual arousal, smooth muscle relaxation is initiated. The health of the endothelium will determine the contribution of eNO to the erectile process.…”
Section: Genital Arousalmentioning
confidence: 99%
“…9 Through fMRI studies, some authors have concluded that the vagus nerve can convey sensory information from cervical stimulation in women with complete SCI, 10 but this has been relatively unexplored. 3 Reflexogenic genital arousal is produced by tactile stimulation to the genitals resulting in afferent stimuli to the spinal cord (afferent input), with some signals following an ascending tract (sensory perception) and others activating the autonomic nuclei S2-S4 resulting in cavernosal nerve activation, smooth muscle relaxation, and tumescence (efferent output). 7 In complete spinal cord lesions above the T10, impulses fail to reach the psychogenic arousal center of T11-L2 and cannot ascend the spinal cord to add to sensory perception.…”
Section: Genital Arousalmentioning
confidence: 99%
“…Lost climactic sensation during ejaculation might also be explained by the fact that these men with lumbosacral lesions cannot experience even mild autonomic hyperreflexia which has been associated with climactic responses in men with SCI. 12,13,18 Yet, the premature nature of ejaculation following lower SCI remains a mystery.…”
Section: Discussionmentioning
confidence: 99%
“…These patients also suffer from severe erectile dysfunction, which is seldom treated successfully with phosphodiesterase inhibitors (sidelnafil, tadalafil, vardenafil), and which usually requires intracavernous injections (papaverine, prostaglandins or trimix) or a combination of treatments. Their PEs may be treated with antidepressive drugs such as selective serotonin reuptake inhibitors (for example, sertraline, fluoxetine, paroxetine), 13 which are known for their side effects on ejaculation, but follow ups would be required to explore the patients' satisfaction with these treatments (for example, the treatments may not help for the already poor sensations felt during ejaculation). Upon satisfaction with selective serotonine reuptake inhibitors (SSRIs), the new Dapoxetine treatment (a short acting SSRI) would be promising, although the drug is not universally available (in particular in North America where it has not received Food and Drug Administation approval).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation